2020
DOI: 10.3390/app10176029
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Atmospheric Kinetic Energy Spectra during the Intensification of Typhoon Lekima (2019)

Abstract: The intensification of Typhoon Lekima (2019) is simulated with the Weather Research and Forecasting model to study the atmospheric horizontal kinetic energy (HKE) spectra and corresponding spectral HKE budgets under the control of real tropical cyclone (TC). The results show that the TC has the ability to modify the canonical atmospheric energy spectrum during its evolution, which is dominated by its rotational mode. With the intensification of Lekima, the HKE spectrum in the troposphere swells over the centra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 36 publications
2
23
0
Order By: Relevance
“…Meanwhile, we also refer to the parameterization schemes by Zheng et al. (2020) who carry out the simulation of typhoon Lekima. The detailed model setup and parameterization scheme used in this paper, which can better simulated typhoon and precipitation, are described as follows.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, we also refer to the parameterization schemes by Zheng et al. (2020) who carry out the simulation of typhoon Lekima. The detailed model setup and parameterization scheme used in this paper, which can better simulated typhoon and precipitation, are described as follows.…”
Section: Methodsmentioning
confidence: 99%
“…In order to get the appropriate model setup and parameterization schemes in the simulation of typhoon "Lekima," some sensitivity tests (not shown in this paper) have been carried out including the initial fields, microphysics scheme and so on. Meanwhile, we also refer to the parameterization schemes by Zheng et al (2020) who carry out the simulation of typhoon Lekima. The detailed model setup and parameterization scheme used in this paper, which can better simulated typhoon and precipitation, are described as follows.…”
Section: Model Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…1(a). The lowest sea level pressure of Lekima was 925 hPa and the highest 10-m maximum wind speed was 54 m/s according to the best-track data of Japan Meteorological Agency (Zheng et al 2019).…”
Section: Study Areamentioning
confidence: 99%
“…These differences between the power-law k −3 and k −5/3 dependences of the atmospheric energy are crucial to understand the role of the different scales. Although the formation mechanisms of the energetic curve are still a topic of research, particularly for the mesoscale k −5/3 slope (Gage, 1979;Tung and Orlando, 2003;Skamarock, 2004;Tulloch and Smith, 2006;Wang et al, 2018;Zheng et al, 2020), the observed atmospheric spectrum has been replicated by many numerical weather prediction (NWP) models (Skamarock, 2004;Hamilton et al, 2008;Skamarock et al, 2014). Understanding the dynamics of the mesoscale HKE spectrum provides knowledge beyond the academic interest and into practical terms, as it is crucial to computing error growth and numerical forecasting system accuracy (Lorenz, 1969;Ricard et al, 2013;Skamarock et al, 2014;Weyn and Durran 2017).…”
Section: Introductionmentioning
confidence: 99%